Assessment of cardiac function in syncopal children without organic causes - Heoungjin Kim; Lucy Youngmin Eun (The Korean Pediatric Society, 2021)
Background Syncope is a common problem in children and adolescents. However, a large proportion of syncope cases have no underlying cause. Purpose This study aimed to identify the factors affecting the severity of syncope using tissue Doppler imaging (TDI). Methods This retrospective study included 61 children and adolescents with syncope who underwent echocardiography. The head-up-tilt test (HUT) was performed when there was a more severe syncopal event. We compared the echocardiographic findings between the execute HUT and nonexecute HUT, negative HUT result and positive HUT result, and normal electrocardiogram (ECG) and abnormal ECG groups. Data were analyzed using an unpaired t test post hoc analysis. Results In the execute and nonexecute HUT groups, the odds ratios were 0.55 for medial E/E' (P=0.040) and 0.64 for lateral E/E' (P=0.049). Comparison of the results of the decreased, normal, and increased groups for lateral E/E' revealed a significant difference in the execution HUT and nonexecute HUT groups (overall, P=0.004; decreased vs. increased, P= 0.003; normal vs. increased, P=0.050). Conclusion Medial E/E' and lateral E/E' were decreased in patients with severe syncopal events. These findings suggest that the presence of left ventricular diastolic deterioration may cause hypoperfusion even in the absence of organic causes and, consequently, increase syncope severity and frequency. The TDI measured by echocardiography can be used as an index to predict syncope recurrence and/or severity.